Studies on monsoon season options for sustainable intensification of annual cereal-based rotations towards nutritional outcomes and resource use efficiency in North-West India - Choudhary, Nisha (Chaudhary Charan Singh Haryana Agricultural University, 2024)
A research trial on ―Studies on monsoon season options for sustainable intensification of annual cereal-based rotations towards nutritional outcomes and resource use efficiency in north-west India‖ was conducted during 2023 kharif season at ICAR-CSSRI Karnal, Haryana. The trial was part of a larger project entitled ―Transforming Agri-Food Systems in South Asia‖ (TAFSSA), which was a collaborative effort between CGIAR-CIMMYT and ICARCSSRI. The primary objective was to study the effect of different cropping systems and management practices on improving productivity, nutritional quality, resource use efficiency, C-budgets and environmental footprints to explore potential opportunities for diversification in north-west Indo-Gangetic plains. The study was redesigned during 2022 on an ongoing experiment set up in 2014 at ICAR-CSSRI, Karnal with seven treatment combinations based on different management arrays of practices over famers practices. These combinations of treatments, referred to as scenarios (Sc1 to Sc7). In accordance with the current resource availability and the impact of climate change, these scenarios included different crops, tillage practices, crop establishment management and residue management. Seven scenarios included: i) puddled transplanted rice (CT-PTR); ii) CT-DSR; iii) ZT-DSR; iv) ZT-maize (PBs); v) ZT-baby corn (PBs); vi) ZTsoyabean (PBs) vii) ZT-pearl millet (PBs). Every scenario was assessed for increasing output, revenue as well as for enhancing adaptability to climate hazards. Table 3.3 shows the scenarios with their descriptions and notations. All scenarios were replicated thrice using a randomized block design.